(untitled) (Scottish Historical and Archaeological Internet Reports, 2011)
The use of extensive environmental and finds sampling techniques has produced a broad picture of occupation in this part of Edinburgh during the later medieval period. Although there were no surviving structures, the finds from the ditch show how a collection of finds and ecofacts can produce a rich portrait when taken as a whole. The lack of medieval deposits on the top of the High Street ridge may have previously caused Edinburgh to be written off in terms of medieval research. However, the potential of the Cowgate and deposits at the base of the slope are just beginning to be tapped.